2020
DOI: 10.1039/d0ra01189d
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of graphene oxide (GO)-anchored Pd/Cu bimetallic nanoparticles usingOcimum sanctumas bio-reductant: an efficient heterogeneous catalyst for the Sonogashira cross-coupling reaction

Abstract: Here we report the synthesis and characterization of graphene oxide anchored Pd–Cu bimetallic nanoparticles by bio reduction method and its application in Sonogashira cross-coupling reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…For GO, the XRD pattern reveals a characteristic reflection peak at 2θ = 9.88°. 43 With regard to pure Ag 3 PO 4 , the diffraction peaks around 20.87, 29.69, 33.28, 36.56, 47.78, 52.68, 55.00, 57.27, 61.64, and 73.86°correspond to (110), ( 200), ( 210), ( 211), (310), ( 222), (320), ( 321), (400), and (332) planes of the cubic crystal phase Ag 3 PO 4 (JCPDS card no. 06-0505).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For GO, the XRD pattern reveals a characteristic reflection peak at 2θ = 9.88°. 43 With regard to pure Ag 3 PO 4 , the diffraction peaks around 20.87, 29.69, 33.28, 36.56, 47.78, 52.68, 55.00, 57.27, 61.64, and 73.86°correspond to (110), ( 200), ( 210), ( 211), (310), ( 222), (320), ( 321), (400), and (332) planes of the cubic crystal phase Ag 3 PO 4 (JCPDS card no. 06-0505).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar catalytic behavior was also observed for Pd-Cu nanoalloys anchored on graphene oxide. 93 Regarding gold-based catalysts, Lambert and co-workers demonstrated that supported zero-valent gold nanoparticles catalyzed the cross-coupling between iodobenzene and phenylacetylene, 94 in contrast to the lack of activity shown by Au(I) and Au(III) supported materials. 95 It was proven that some leaching of ionic gold species into the liquid phase during the coupling happened, but this phase did not exhibit any catalytic activity, indicating that the Sonogashira reaction shows a surface-like reactivity.…”
Section: Sonogashira Couplingmentioning
confidence: 99%
“…[4] Accordingly, graphene incorporated with several metals (Ag, Cu, Pd, Zn, Mn, Fe, Ni, Pt, Cd, Co etc.) to produce variety of green synthesized NCs [5][6][7][8][9][10][11][12] that found large scope for research in catalytic reduction, [13] photocatalytic dye degradations, [14][15] electrochemical capacitors, [16] electrocatalyst, [17] supercapacitors, [18] and biological applications like antibacterial, [5][6][7][19][20][21] antioxidant, [21] antimicrobial activities [8-9,22,] with enhanced performances.…”
Section: Introductionmentioning
confidence: 99%